2022
DOI: 10.5194/isprs-archives-xlvi-2-w1-2022-267-2022
|View full text |Cite
|
Sign up to set email alerts
|

Built Heritage Visualizations in Immersive Environments to Support Significance Assessments by Multiple Stakeholders

Abstract: Abstract. In recent years, technological advances in game engines allowed researchers to propose methodological frameworks for integrating digital models of the built heritage in Virtual (VR), Augmented (AR) and Mixed Reality environments. Among other benefits, specific applications have demonstrated the potential of such immersive environments to raise awareness about the significance of historical objects, share associated knowledge and facilitate its collaborative management. Based on the necessity to retri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
1
0
Order By: Relevance
“…Refs. [55,175] suggest data in a BIM model could be shared via VR to reduce intervention errors on construction sites and aid future maintenance works. Ref.…”
Section: Ar and Vrmentioning
confidence: 99%
See 3 more Smart Citations
“…Refs. [55,175] suggest data in a BIM model could be shared via VR to reduce intervention errors on construction sites and aid future maintenance works. Ref.…”
Section: Ar and Vrmentioning
confidence: 99%
“…Another stream of research has suggested the use of VR to enable the population of the geometric model with additional data remotely, a development partially instigated by the COVID-19 pandemic [70,175]. This technique has been successful, with [177] demonstrating that a VR tour allowed students on their 'survey education' course to make meaningful observations on the condition of a temple in China.…”
Section: Ar and Vrmentioning
confidence: 99%
See 2 more Smart Citations
“…In the last years, thanks to the development of more and more powerful hardware technologies and software, able to exploit both the computational skills and the image processing, the dissemination through digital tools in the Heritage field have been developing in an increasingly extensive way [Joannides 2017]. In the field of digital culture related to heritage, the strands are intertwined concerting experiences that can bring to common factor historical, architectural and cultural issues declined through new experiences of storytelling mediated by the experiences of Virtual, Augmented or Mixed Reality [Russo 2021;Teruggi, Fassi 2021;Jouan et al 2022]. The experience of digital fruition, or better, totally viral if not entirely immersive, has become part of museums and institutions, places that open their contents to an increasing number of scholarly enthusiasts or simple users with a thirst for learning [Aiello 2019;Spallone et al 2022].…”
Section: Introductionmentioning
confidence: 99%